The profile of long-chain fatty acids in serum phospholipids: a possible indicator of copper status in humans - Cunnane, SC (The American journal of clinical nutrition, 1988)
In previous reports of experimental copper depletion in humans, it was difficult to reliably demonstrate biochemically that there was Cu depletion. In view of the changes in serum phospholipid fatty acid profiles in Cu-deficient rats, it was considered worthwhile to determine the effect of Cu depletion in humans on serum fatty acid profiles. Serum samples from the Cu-depletion study of Reiser et al were analyzed for phospholipid fatty acid composition. After the participants had been on the low copper diet for 11 wk, serum phospholipids contained 27% less oleic acid, 38% more arachidonic acid, and 94% more docosahexaenoic acid (all p less than 0.01) than samples taken from the same subjects before Cu depletion. These fatty acid changes were of a similar direction and magnitude to those in moderately Cu-depleted rats and may be useful as an index of moderate Cu depletion in humans.